2005
DOI: 10.4049/jimmunol.175.7.4383
|View full text |Cite
|
Sign up to set email alerts
|

Gs Protein-Coupled Adenosine Receptor Signaling and Lytic Function of Activated NK Cells

Abstract: The effect of adenosine and its analogues on the cytotoxic activity of IL-2-activated NK cells was investigated. Adenosine is an endogenous ligand for four different adenosine receptor (AdoR) subtypes (AdoRA1, AdoRA2A, AdoRA2B, and AdoRA3). Increased concentrations of adenosine were found in ascites of MethA sarcoma or in culture medium of 3LL Lewis lung carcinoma growing under hypoxic conditions. We hypothesize that intratumor adenosine impairs the ability of lymphokine-activated killer (LAK) cells to kill tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 25 publications
6
126
0
Order By: Relevance
“…PDE is responsible for the conversion of the signaling molecule cyclic adenosine monophosphate (cAMP) to five prime adenosine monophosphate (5'-AMP), and inhibition of PDE can cause increases in the levels of cellular cAMP. This is significant in that Goto et al 1983 and Raskovalova et al 2005 established that increases in cellular cAMP levels either through the increased production of or the addition of exogenous cAMP caused a decrease in the NK cell mediated lysis of NK cell specific targets (Goto et al 1983;Raskovalova et al 2005). Thus a potential target through which atrazine may effect on NK cell lytic function is the PDE protein (Roberge et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…PDE is responsible for the conversion of the signaling molecule cyclic adenosine monophosphate (cAMP) to five prime adenosine monophosphate (5'-AMP), and inhibition of PDE can cause increases in the levels of cellular cAMP. This is significant in that Goto et al 1983 and Raskovalova et al 2005 established that increases in cellular cAMP levels either through the increased production of or the addition of exogenous cAMP caused a decrease in the NK cell mediated lysis of NK cell specific targets (Goto et al 1983;Raskovalova et al 2005). Thus a potential target through which atrazine may effect on NK cell lytic function is the PDE protein (Roberge et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Two of these are activin receptors (Acvrl1 and Acvr2a) that recognize this member of the transforming growth factor-␤ superfamily, a factor that may be secreted by Th2 cells (69) and by dendritic cells (70). The expressed adenosine receptor, Adora2b, can receive signals important to NK cell activity and regulation (71). A receptor capable of sensing extracellular nucleotides released in inflammation is also present (P2ry6) (72).…”
Section: Discussionmentioning
confidence: 99%
“…As earlier mentioned, hypoxia is one of the major causes for production of adenosine; therefore, adenosine is found at higher concentration in these hypoxic sites associated with tumor. In vitro studies with 3LL Lewis lung carcinoma cells have shown that hypoxia stimulates adenosine production by tumor cells [61] (Fig. 3).…”
Section: Adenosine and Macrophage Interaction In Tumor Microenvironmentmentioning
confidence: 99%
“…Williams Adenosine, CADO, and A 2A receptor agonists CGS, and 5-N-ethylcarboxamide adenosine (CGS21680 and NECA) inhibit both the perforin-and FasL-mediated lysis of tumor cells by lymphokine-activated killer (LAK) cells [61]. Various similar studies, in which LAK cells were isolated from deficient A 1 and A 3 receptors have confirmed that these adenosine receptors do not play any role in the adenosinemediated suppression of NK cell activity in tumor environment [143].…”
Section: Adenosine and Dendritic Cells Interaction In Tumor Environmentmentioning
confidence: 99%